Challenges of the Curricular Reforms vs. the Imperative of the Social Cohesion - Cecilia Braslavsky (Universidad Autónoma de Madrid, 2018)
In the begginings of XXI century, under the impact of the paradoxes of the globalización (UNESCO-IBE, 200a'). The human societies never before experienced a greater growth of scientific and technological knowledge at the same time that the difficulties for the implementation in benefit of all the population are so significant. This new reality has created a challenge for the education: How it can be still possible to transform the necessity of emigration of one into a real potentiality for the mutual benefit of the countries of origin and the countries of residence? How to avoid the risk of a new Average Age? How to avoid the deepening of communication hollows? How the world could accept and really integrate the nomadic workers, instead of persecuting them? In order to respond to these questions, one of the ways could be the construction of "glocales" identities in an multiethnic world and a multicultural society: the global society. Original reference: Braslavsky, C. (2004). Desafíos de las reformas curriculares frente al imperativo de la cohesión social. En: UNESCO/BIE. Reforma Curricular y Cohesión Social en América Latina. Paris, Ginebra: UNESCO/IBE.